Cytoscape A Tool to Visualize Protein-Protein interactions using Eugenol, a Phytochemical of Ocimum sanctum L - Surender, Vanitha; Sharma, Tanushree (Nepal Journal of Science and Technology, 2023)
Eugenol (4-hydroxy-3-methoxy-allylbenzene) is an important bioactive compound found in various medicinal plants and has been extensively investigated for its pharmacological properties. Apart from its anaesthetic and analgesic properties, this phenolic compound has antimicrobial, anti-inflammatory, anticancer and antioxidant properties. One of the promising candidates with versatile applications in designing new drugs will be Eugenol for its pharmacological effects. While the metabolism and pharmacokinetics of Eugenol have been studied in humans, still there is lack of data available on its precise mode of action and its impact on system level protein networks. To identify the action of Eugenol on protein interaction network, an interactome was constructed using STRING and Cytoscape tools, based on 98 key proteins extracted from PubMed literatures. Swiss Target Prediction was used to predict the possible macromolecular targets in humans. It was predicted that the target classes included 20% enzymes, secreted protein, and Family A G- protein coupled receptors, 13.3% of Ligand-gated ion channel and 6.7% of kinase, eraser, lyase and oxidoreductases. Further, using the Cytoscape 3.9.1 version in-silico study, it could be observed that 92 nodes in total were connected with 61 edges with a clustering coefficient of 0.369. Using a phytochemical Eugenol, the possible network analysis has been predicted. Evaluating the network among the other phytochemicals of Ocimum sanctum could help us to investigate the role played by these key phytochemicals at gene and molecular level and can help us explore their interference in disease patterns in humans.